2021
DOI: 10.1021/acssynbio.1c00007
|View full text |Cite
|
Sign up to set email alerts
|

Switchable CAR-T Cells Outperformed Traditional Antibody-Redirected Therapeutics Targeting Breast Cancers

Abstract: Various antibody-redirected immunotherapeutic approaches, including antibody-drug conjugates (ADCs), bispecific antibodies (bsAbs), and chimeric antigen receptor-T (CAR-T) cells, have been devised to produce specific activity against various cancer types. Using genetically encoded unnatural amino acids, we generated a homogeneous Her2-targeted ADC, a T cellredirected bsAb, and a FITC-modified antibody capable of redirecting anti-FITC CAR-T (switchable CAR-T; sCAR-T) cells to target different Her2-expressing br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…GPC3 and ERBB2, as common solid tumor target antigens, are frequently diffused in various tissues and organs; therefore, reducing the damage to important organs while targeting these antigens is a top priority. Other target antigens have also shown potential in CAR-T therapy, such as IGF1R ( 39 , 40 ), CD1A ( 41 , 42 ), CCR9, and CXCR4. Our results showed that IGF1R is widely expressed in various lineages from three germ layers, while the expression of CD1A, CCR9, and CXCR4 is relatively limited to immune cell types ( Supplementary Figure 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…GPC3 and ERBB2, as common solid tumor target antigens, are frequently diffused in various tissues and organs; therefore, reducing the damage to important organs while targeting these antigens is a top priority. Other target antigens have also shown potential in CAR-T therapy, such as IGF1R ( 39 , 40 ), CD1A ( 41 , 42 ), CCR9, and CXCR4. Our results showed that IGF1R is widely expressed in various lineages from three germ layers, while the expression of CD1A, CCR9, and CXCR4 is relatively limited to immune cell types ( Supplementary Figure 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…T cells simultaneously engineered with CAR to recognize dual antigens have been successfully applied to redirect various hematological and solid malignancies [14,15]. Preclinical studies have shown that this approach results in increased antitumor function compared with that obtained with CAR-T cells specific for one TAA [16,17]. Although a few studies explored trispecific antibodies (tsAbs) with the feasibility of eliciting an anticancer response for dual-TAA targeting [18][19][20][21], researchers have not yet determined whether the constructs were well designed based on the molecular events relating to optimal bsAb configuration.…”
Section: Ivyspringmentioning
confidence: 99%
“…There are many exciting areas of ongoing HER2-directed research, including novel ADCs (ARX788 and RC48), 65,66 bi-specific antibodies, 67,68 and chimeric antigen receptor T-cells. 6972 A number of phase III trials exploring the role of new HER2-directed agents for advanced and earlier stage BC are also underway (Table 4). In the advanced setting, a number of novel agents are being assessed for patients with progressive disease on prior HER2-directed therapy, including tucatinib combined with T-DM1 (HER2CLIMB-02, NCT03975647), T-DXd (DESTINY-Breast02, NCT03523585), and the trastuzumab ADC BAT8001 (NCT04185649).…”
Section: Discussionmentioning
confidence: 99%